Economic Security of Poland - Taksás, Balázs; Waszkiewicz, Grzegorz; Gontarczyk, Mariusz; Zelkowski, Jarosław (Public Finance Quarterly, 2024)
The aim of this research is to create a relatively easy-to-apply, yet complex and complete model for measuring levels of economic security, one that incorporates risks in supply, ﬁnance, labor market, technology, sales, economic policy, and mobilization, thus comprehensively evaluating the economic security situation of a country and the danger of risk activation. The development of this conceptual model and the risk groupings was based on several historical and contemporary economic dysfunction and crisis studies (approximately one hundred). The applied methodology takes into account the diﬀerent risk-averse or risk-tolerant preferences of various societies. It also considers the eﬀect of economic cycles on economic indicators. Meanwhile, simple mathematical calculations ensure ease of application, making it readily adaptable not only for academics and researchers, but also for any governmental entity, or non-governmental organization. With the help of this model and thirteen selected indicators, we subjected Poland’s economic security situation for the period 2010-2019 to comprehensive analysis. We then drew conclusions on how the level of risk in diﬀerent subsystems changed during this relatively calm period.